2013
DOI: 10.4187/respcare.02355
|View full text |Cite
|
Sign up to set email alerts
|

Gorham Syndrome With Postoperative Respiratory Failure and Requiring Prolonged Mechanical Ventilation

Abstract: Gorham syndrome is a rare disease that presents as progressive osteolysis, and may affect any part of the skeleton. The pathologic process involves the replacement of normal bone by aggressively expanding but non-neoplastic vascular tissue, resulting in massive osteolysis of the adjacent bone. If the spine and ribs are affected, the subsequent kyphosis and chest wall deformity may cause severe restrictive ventilatory impairment. We report a 34-year-old male with Gorham syndrome presenting as progressive kyphos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…As sclerotherapy, pleurodesis was performed using OK-432, talc, and minocycline. 395,[397][398][399]404,408,411,[416][417][418] There were patients who responded markedly to sclerotherapy alone and sclerotherapy combined with surgical procedures such as pleural decortication or local radiotherapy. There was no mention about complications of sclerotherapy.…”
Section: Conditions Of Patientsmentioning
confidence: 99%
“…As sclerotherapy, pleurodesis was performed using OK-432, talc, and minocycline. 395,[397][398][399]404,408,411,[416][417][418] There were patients who responded markedly to sclerotherapy alone and sclerotherapy combined with surgical procedures such as pleural decortication or local radiotherapy. There was no mention about complications of sclerotherapy.…”
Section: Conditions Of Patientsmentioning
confidence: 99%
“…As sclerotherapy, pleurodesis was performed using OK-432, talc and minocycline. 395,[397][398][399]404,408,411,[416][417][418] There were patients who responded markedly to sclerotherapy alone and sclerotherapy combined with surgical procedures such as pleural decortication or local radiotherapy. There was no mention of complications of sclerotherapy.…”
Section: Commentsmentioning
confidence: 99%
“… 6 To the best of our knowledge, 13 cases of GD of spine have been reported after 2005. 8 20 21 22 23 24 25 26 27 28 29 30 31 A brief review of these cases with treatment and outcome has been shown in Table 2 . Out of the total 41 reported cases of GD of spine, cervical spine is the most commonly affected with 11 cases involving only cervical spine and additional 6 cases involving cervicothoracic spine.…”
Section: Discussionmentioning
confidence: 99%